Diastereoselective [2,3]-Sigmatropic Rearrangement of N-Allyl Ammonium Ylides - Murre, Aleksandra; Erkman, Kristin; Kaabel, Sandra; Järving, Ivar; Kanger, Tõnis (Synthesis, 2019)
A rapid and diastereoselective method was developed for the [2,3]-sigmatropic rearrangement of N-allyl ammonium ylides, affording products in up to 95% isolated yields and up to 97:3 dr; most of the desired products were formed within 1 minute. For the asymmetric reaction, a chiral auxiliary was introduced to the starting compound, affording the rearrangement product with high diastereoselectivities.
Keywords: [2,3]-sigmatropic rearrangement; ammonium ylide; auxiliary; diastereoselectivity; oxazolidinyl group; α-amino ketones